The effects of metacognitive learning strategies of third year high school students' reading comprehension - Borromeo, Josefina Ante 1963- (1998)
It was hypothesized in this study that students taught to employ metacognitive learning strategies (MCLS) would show better reading comprehension results than their peers taught with conventional strategies. Better comprehension results would improve the following reading skills: making inferences, summarizing, identifying main ideas, predicting, vocabulary building, and over-all reading comprehension. According to the findings, MCLS have positive effects on third year high school students' reading comprehension skills.